Socio-demographic factors associated with knowledge and uptake of family planning among women of reproductive age in a Rural Community of Abuja, Nigeria - Saleh, Fatima; Raji, Mansur Olayinka; Oche, Mansur; Kaoje, Aminu Umar; Tunau, Karima (Penerbit Universiti Kebangsaan Malaysia, 2018)
Nigeria has a population of about 180 million, estimated to double in 22 years due to low uptake of family planning services. Low utilization of family planning is the major factor associated with high fertility pattern in Nigeria. This trend is higher among rural women in Northern Nigeria. Without a thorough understanding of, and due attention to the local context, utilization of family planning may continue to be low. Identification of correlates of family planning would be invaluable in designing strategies for ultimately improving uptake of family planning services. This study became relevant as no previous study on family planning has been carried out in Ushafa Community. The study was conducted at Ushafa community, a rural community, located in Bwari Area Council on the northern axis of the Federal Capital Territory (FCT) of Nigeria. The study was a descriptive cross-sectional study, conducted among women of reproductive age (15-49 years) who were permanent resident of Ushafa Community. Using proportion of contraceptive usage of 16% from a previous study, 240 women were recruited into the study by systematic sampling technique. Data was collected by means of a structured interviewer administered questionnaire, data was entered and analysed using statistical package for social sciences (SPSS) version 20. All tests were conducted using 2 tails while level of significance was set at 0.05. About a quarter of respondents (26.3%) knew that amenorrhoea could be a side effect of oral contraceptive pills, 51.1% knew that oral contraceptive pills must be taken daily, 58% were not using any form of family planning. Age (χ2 = 8.382, p = 0.01) and marital status (χ2 = 8.915, p = 0.01) were significantly associated with family planning knowledge. Level of education was significantly associated with current use of family planning (χ2 = 10.78, p = 0.03). Educational status was significantly associated with likelihood of using family planning in the future (χ2 = 8.64, p = 0.04). Although the respondents had fairly good knowledge of family planning, the study observed some misconceptions especially with respect to side effects and methodology of use of the commodities. Low uptake of family planning was observed among the respondents. Age and marital status were significantly associated with family planning knowledge; level of education was significantly associated with current use of family planning. There is need for incorporation of facts on usage and side effects of family planning in message disseminated by health workers in health facilities in Ushafa Community so as to correct misconceptions.